Mechanisms of multimodal sensing by extracellular Ca(2+)-sensing receptors: a domain-based survey of requirements for binding and signalling - Khan, Mahvash A (Blackwell Publishing Ltd, 2010)
In this article we consider the molecular basis of sensing and signalling by the extracellular calcium-sensing receptor. We consider the nature of its ligands and sensing modalities, the identities of its major protein domains and their roles in sensing, signalling and trafficking as well as the significance of receptor homo- and hetero-dimerization. Finally, we consider the current, incomplete, state of knowledge regarding the requirements for ligand-specific signalling. This article is part of a themed section on Molecular Pharmacology of GPCR. To view the editorial for this themed section visit http://dx.doi.org/10.1111/j.1476-5381.2010.00695.x